Microbial Community Dynamics During the Non-filamentous Fungi Growth-Based Fermentation Process of Miang, a Traditional Fermented Tea of North Thailand and Their Product Characterizations - Unban, Kridsada; Khatthongngam, Nuttapong; Pattananandecha, Thanawat; Saenjum, Chalermpong; Shetty, Kalidas; Khanongnuch, Chartchai (Frontiers in Microbiology, 2020)
Miang, a traditional fermented tea leaves (Camellia sinensis var. assamica) consumed in northern Thailand, was simulated in laboratory conditions using non-filamentous fungi process (NFP) and microbial community were periodically investigated for over 6 months of fermentation by both culture dependent and independent techniques. The viable cell number of lactic acid bacteria (LAB), yeast and Bacillus enumerated by culture-dependent technique were markedly surged over 3 days of initial fermentation and then smoothly declined by the end of fermentation. LAB was found as the main microbial population throughout fermentation period followed by yeast and Bacillus. High-throughput sequencing of microbial community during fermentation revealed that Firmicutes (86.9-96.0%) and Proteobacteria (4.0-12.4%) were the dominant bacterial phyla, whereas Ascomycota were found to be the main fugal phylum with an abundance of over 99% in the fungal community. The dominant bacterial family was Lactobacillaceae (39.7-79.5%) followed by Acetobacteraceae, Enterobacteriaceae, Bacillaceae, Aeromonadaceae, Staphylococcaceae, Moraxellaceae, Clostridiaceae, Exiguobacteraceae, Streptococcaceae and Halomonadaceae. Meanwhile, the main fungal family was incertae sedis Saccharomycetales (75.6-90.5%) followed by Pichiaceae, Pleosporaceae, Botryosphaeriaceae, Davidiellaceae, Mycosphaerellaceae and Saccharomycodaceae. In addition, Lactobacillus (29.2-77.2%) and Acetobacter (3.8-22.8%), and the unicellular fungi, Candida (72.5-89.0%) and Pichia (8.1-14.9%), were the predominant genera during the fermentation process. The profiles of physical and chemical properties such as Miang texture, pH, organic acids, polysaccharide degrading enzyme activities and bioactive compounds have rationally indicated the microbial fermentation involvement. -Mannanase and pectinase were assumed to be the key microbial enzymes involved in Miang fermentation process. Total tannin and total polyphenol contents were relatively proportional to the antioxidant activity. Lactic acid and butyric acid reached maximum of 50.9 and 48.9 mg/g dry weight (dw) at 9 and 63 days of fermentation, respectively. This study provided essential information for deeper understanding of Miang fermentation process based on the chemical and biological changes during production.